2009
DOI: 10.1111/j.1600-0463.2008.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of cyclooxygenase‐2 in urothelial carcinoma in conjunction with tumor‐associated‐macrophage infiltration, hypoxia‐inducible factor‐1α expression, and tumor angiogenesis

Abstract: Overexpression of Cyclooxygenase-2 in Urothelial Carcinoma: in conjunction with tumor-associated-macrophage infiltration, hypoxia-inducible factor-1a expression, and tumor angiogenesis. APMIS 2009; 117:176-84. This study examines whether the expression of cyclooxgenase-2 (COX-2) in urothelial carcinoma (UC) is associated with macrophage infiltration, hypoxia-inducible factor-1a (HIF-1a) expression and angiogenesis. We investigated the expression of COX-2 associated with HIF-1a and performed double immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 32 publications
1
27
0
1
Order By: Relevance
“…This interdependence was confirmed in the present results, where COX-2 intensity, but not the extension grade, was associated with macrophage infiltration in malignant melanomas (P = 0.015), specifically of cutaneous localization (P =0.033). Similar relationships were described in humans for urothelial carcinoma [48], colorectal carcinomas [49], hepatocellular carcinoma [50] and prostate carcinoma [51]. Several mechanisms underlying COX-2 and macrophage correlation have been proposed.…”
Section: Discussionsupporting
confidence: 55%
“…This interdependence was confirmed in the present results, where COX-2 intensity, but not the extension grade, was associated with macrophage infiltration in malignant melanomas (P = 0.015), specifically of cutaneous localization (P =0.033). Similar relationships were described in humans for urothelial carcinoma [48], colorectal carcinomas [49], hepatocellular carcinoma [50] and prostate carcinoma [51]. Several mechanisms underlying COX-2 and macrophage correlation have been proposed.…”
Section: Discussionsupporting
confidence: 55%
“…Another study also reported a significant correlation between TAM density and microvessel density as well as poor prognosis. 83 With regard to bacille de Calmette et Guérin (BCG) therapy, which is the gold standard of bladder cancer treatment, a high infiltration of CD68 + TAMs was related to an increased risk of recurrence in patients with non-muscleinvasive urothelial cancer before BCG immunotherapy. 84 Analysis of patients with bladder carcinoma in situ who received BCG therapy indicated frequent recurrences in patients with a high density of CD68 + TAMs.…”
Section: Urothelial Cell Carcinoma Of the Bladdermentioning
confidence: 99%
“…[82][83][84][85][86] Recurrence after BCG therapy occurred frequently in patients with a high density of TAMs. 84,85 Endometrial caner Poor prognosis High TAM density correlated with tumor progression with or without link to poor prognosis.…”
Section: Poor Prognosismentioning
confidence: 99%
“…HIF-2·, originally called endothelial PAS protein-1 (EPAS1), shares close amino acid sequence homology and similar pharmacological and regulatory properties with HIF-1· (24,25). In addition, there is increasing evidence that cyclooxygenase-2 (COX-2) promotes tumor angiogenesis by regulating HIF-1· and VEGF, even in cases of gastric cancer (25)(26)(27). Furthermore, prostaglandin E2, a product of COX-2, is directly involved in the formation of new blood vessels (11).…”
Section: Introductionmentioning
confidence: 99%